"It Was a Bum Rap": Self-Reports of Being Erroneously Arrested in a National Sample. (September 2014) - Pollock, Wendi; Menard, Scott
Individual-level predictors of erroneous arrest for illegal behavior are investigated using a national level, probability sample. The analysis specifically examines whether being a "usual suspect" based on previous criminal behavior and being male; "guilt by association" based on the illegal behavior of one's friends; academic achievement; and sociodemographic variables including ethnicity and socioeconomic status, impact the likelihood of being erroneously arrested for a crime. Results suggest that officers may be erroneously arresting minorities and individuals who have low academic achievement. Implications for policy and future research are considered.